A Design Framework for Tool Support of Performance Management for Clinical Practice - Mata, Pilar (Université d'Ottawa / University of Ottawa, 2021)
Performance management is essential to any organization that wants to monitor progress towards strategic goals and proactively address gaps identified during the implementation of the strategy. Healthcare organizations have implemented tool support for performance management in response to increasing demand for accountability and transparency on quality of care indicators or to promote continuous improvements in quality of care. However, there is little guidance in the literature and the industry on how to operationalize a performance management strategy for clinical practice with appropriate tool support. In this thesis we propose a framework for design of tool support for performance management of clinical practice. The framework includes: a Conceptual Model of the relevant entities and actors for performance management of clinical practice; a Performance Management Participation View of what tool-supported tasks performed by what actors in what processes are needed to enact performance management for the clinical practice; a Performance Measurement View of what clinical practice goals are measured by what indicators in which tool-supported tasks for the clinical practice; and a Tool Support Design Methodology for the design, implementation and validation of tools to support performance management of the clinical practice. The research methodology followed for this thesis was design science research. The framework was developed and evaluated iteratively in a series of three case studies conducted in collaboration with three sets of health care professionals responsible for clinical practice in these areas: resident training, discharge management, and care of frail patients in a long term care residence.
Keywords: Performance Management; Healthcare; Design Frameworks for Healthcare IT; Tool Support of Performance Management for Clinical Practice; Tool Support Design Methodology